Cause of Death in Patients in Radiation Oncology - Domschikowski, Justus; Koch, Karoline; Schmalz, Claudia (Frontiers in Oncology, 2021)
Background: The accurate attribution of death in oncologic patients is a difficult task. Their death is often attributed to their underlying cancer and hence judged cancer related. We hypothesised that even though their cancers were advanced, not all had died simply because of cancer. Methods: 105 patients were included in this retrospective analysis. Patient data was collected from digital and paper based records. Cause of death was assessed from death certificate and compared to the medical autopsy report. Autopsy reports were further analysed for class I and II discrepancies. Results: From 105 included patients, in 56 cases (53%) consent to autopsy was given. 32/56 were palliatively sedated and 75% died cancer-related as confirmed by autopsy. Most common cause of death by autopsy report was multi-organ-failure followed by a combined cause of tumor and infection, predominantly lung cancer with pneumonia. 21/56 cases (37%) showed major missed diagnoses. 7 cases showed class I, 10 class II and 4 both discrepancies. Conclusions: The majority but not all patients had died because of their advanced cancer supporting a holistic patient view. Further, the rate of discrepancies did not differ from other oncologic series even though half of our population was palliatively sedated and nearly all referred for palliative treatment. However, in our opinion the classification system should be adapted for palliative patients refusing further diagnostics to increase precision in discrepancy reporting.